Enhancing emergency department triage for older patients: a prospective study on the integration of the identification of seniors at risk - Lanxin Ouyang; Shuzhen Yu; Ziwei Hu; Yin Lin; Di Liu (BMC Emergency Medicine)
Abstract Background Older adults are a growing demographic in emergency departments (EDs) worldwide, yet traditional triage systems often fail to account for their unique risks, leading to under-triage and adverse outcomes. The Identification of Seniors at Risk (ISAR) tool offers a pragmatic approach to enhance risk stratification, but its integration into ED triage systems remains underexplored. Methods This prospective single-center observational cohort study assessed older patients (≥ 65 years) using both the standard ED triage system and the ISAR scale. After a 30-day follow-up, triage levels were retrospectively adjusted upward by one level for patients with ISAR scores ≥ 2. The predictive accuracy of the revised triage system was compared to the original system using logistic regression and receiver operating characteristic (ROC) curve analysis. Results Among 973 patients completing follow-up, 38.1% had an ISAR score ≥ 2. Older patients (≥ 75 years) were more likely to be classified as high risk and had significantly higher rates of adverse outcomes, including ICU admission and 30-day mortality. The revised triage system slightly improved discriminative ability in patients aged ≥ 65 years (AUC 0.697 to 0.714), with stable performance maintained in those aged ≥ 75 years (AUC 0.703). Sensitivity declined slightly, while specificity improved. Conclusion Integrating ISAR into ED triage modestly enhanced the identification of older patients at risk for short-term adverse outcomes, particularly among those aged ≥ 65 years. These findings support the value of incorporating geriatric screening into routine triage to enable more tailored risk stratification. Further studies are needed to evaluate implementation feasibility across different healthcare settings and to inform integration into routine practice. Clinical trial number Not applicable.